Treatment with low‐dose tacrolimus inhibits bleeding complications in a patient with hereditary hemorrhagic telangiectasia and pulmonary arterial hypertension. (1st November 2018) - Sommer, N; Droege, F; Gamen, KE; Geisthoff, U; Gall, H; Tello, K; Richter, MJ; Deubner, LM; Schmiedel, R; Hecker, M; Spiekerkoetter, E; Wirsching, K; et al.
Abstract : Pulmonary arterial hypertension (PAH) can be found in patients suffering from a loss‐of‐function mutation of the gene encoding for the activin receptor‐like kinase 1 (ALK‐1), a bone morphogenetic protein (BMP) type 1 receptor. Interestingly, ALK‐1 mutations also lead to hereditary hemorrhagic telangiectasia (HHT), an autosomal dominant disease characterized by arteriovenous malformations (AVMs) leading to potentially life‐threatening bleeding complications such as epistaxis. Current therapeutic options for both diseases are limited and often only temporary or accompanied by severe side effects. Here, we report of a patient with a mutation of the ALK‐1 gene suffering from both HHT and PAH. Recently, it was shown that tacrolimus increased ALK‐1 signaling and had beneficial effects in selected end‐stage PAH patients. We thus hypothesized that treatment with tacrolimus may prevent disease progression in this patient. Surprisingly, treatment with low‐dose tacrolimus dramatically improved his HHT‐associated epistaxis but did not attenuate progression of PAH.